Healthcare costs of colorectal cancer screening and events following colonoscopy among commercially insured average-risk adults in the United States. (4th March 2022) - Fisher, Deborah A.; Princic, Nicole; Miller-Wilson, Lesley-Ann; Wilson, Kathleen; Limburg, Paul
Abstract: Objective: To examine the healthcare costs associated with colorectal cancer (CRC) screening and the frequency and costs of events potentially related to colonoscopy among average-risk adults. Methods: In this cohort study, adults (ages 50–75 years) with CRC screening between 1/1/2014 and 6/30/2019 (index = earliest test) were selected from the IBM MarketScan Research databases. Individuals at above-average risk for CRC or with prior CRC screening were excluded. Frequency of utilization was reported by screening type: colonoscopy, fecal immunochemical test (FIT), fecal occult blood test (FOBT), multi-target stool DNA (mt-sDNA). For colonoscopy, frequency and costs of potential events were reported overall, by event type, and by an individual event in the 30 days after colonoscopy. Results: Among the 333, 306 average-risk adults, colonoscopy was the most common CRC screening modality (70.6%), followed by FIT (17.7%), FOBT (8.1%), and mt-sDNA (3.2%). The mean cost of a colonoscopy procedure was 2, 125 and the mean out-of-pocket costs were 79. Serious gastrointestinal (GI) events were observed in 1.3% of individuals with colonoscopy, 1.9% had other GI events, and 1.2% had an incident cardiovascular event. Mean event-related costs were 2, 631 among individuals with a serious GI event, 1, 774 among individuals with any other GI event, and 4, 234 among individuals with a cardiovascular event. Conclusions: This study provides updated and more detailed information regarding the costs of CRC screening and potential colonoscopy events based on a comprehensive review of a robust claims dataset.